Pandangan Islam Terhadap Implementasi Hybrid Contract Di Hotel Horison Sagita Balikpapan - Wiwit Agustina (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
In the business world, trade is one of the most important things in human life. Everyone always needs prosperity and wealth to meet their needs. With this goal in mind, people compete for wealth through their businesses. if a company is based or based on religious principles, it is of course very closely related to the norms associated with Islamic institutional economics. Because sharia-based economic activities are economic practices that are based on Islamic values, actors need to orient themselves in consumption, production and operations. The Islamic View of the Implementation of Hybrid Contracts which has innovated is the author's basis for researching the validity of the contracts made by the Horison Sagita Balikpapan hotel, where the purpose of this research is to examine multi-contract transactions (Hybrid Contracts) in the Horison Sagita Balikpapan hotel. In this study the authors used an empirical juridical approach, combining primary data and data in the field so that theory and practice were found to be compatible. Based on the results of this study, after making adjustments to the provisions of the multiple contracts that are prohibited, it can be concluded that the Hybrid Contract transaction in booking a room including dining at the Horison Sagita Balikpapan Hotel is not at all included in the multi-contract category which is prohibited. Thus the Hybrid Contract transaction in the Booking of the Incluede Room is permissible and does not violate sharia provisions. In addition, this transaction can provide convenience for hotel managers and consumers. Keyword: Islamic View, Hybrid Contract, Hotel Rental